2012
DOI: 10.1523/jneurosci.1892-12.2012
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Working Memory Storage and Elevated Activity as Measured with Functional Magnetic Resonance Imaging

Abstract: Does the sustained, elevated neural activity observed during working memory (WM) tasks reflect the short-term retention of information? Functional magnetic resonance imaging (fMRI) data of delayed-recognition of visual motion in human participants were analyzed with two methods, a general linear model (GLM) and multi-voxel pattern analysis (MVPA). Although the GLM identified sustained, elevated delay-period activity in superior and lateral frontal cortex and in intraparietal sulcus (IPS), pattern classifiers w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

48
265
6
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 340 publications
(330 citation statements)
references
References 59 publications
(78 reference statements)
48
265
6
3
Order By: Relevance
“…Harrison and Tong have shown that even if the overall delay activity is low in human visual cortices, orientations held in WM can still be clearly decoded from the activity patterns [29] . This coincides with the neurophysiological data from monkey SI cortex during the delay period of a tactile WM task noted above [26] .Furthermore, recent neuroimaging studies have shown that trial-specifi c stimulus information can be decoded from sensory cortices but not from the PFC [31][32][33] .Not only do sensory cortices represent fine-tuned modality-specifi c sensory information during WM, but they can also be tuned to other sensory modalities (crossmodality) after associative training. Zhou and Fuster have shown that the sustained delay activity of SI neurons in monkeys is selective for visual stimuli in a visual-tactile cross-modal WM task [34] (Fig.…”
supporting
confidence: 85%
See 3 more Smart Citations
“…Harrison and Tong have shown that even if the overall delay activity is low in human visual cortices, orientations held in WM can still be clearly decoded from the activity patterns [29] . This coincides with the neurophysiological data from monkey SI cortex during the delay period of a tactile WM task noted above [26] .Furthermore, recent neuroimaging studies have shown that trial-specifi c stimulus information can be decoded from sensory cortices but not from the PFC [31][32][33] .Not only do sensory cortices represent fine-tuned modality-specifi c sensory information during WM, but they can also be tuned to other sensory modalities (crossmodality) after associative training. Zhou and Fuster have shown that the sustained delay activity of SI neurons in monkeys is selective for visual stimuli in a visual-tactile cross-modal WM task [34] (Fig.…”
supporting
confidence: 85%
“…Interestingly, using MVPA, Christophel and Haynes have decoded motion patterns not only from visual areas, but also from SI, even if the task is a pure visual WM task and the visual-spatial pattern is without any association with touch [37] . They have suggested that the tactile cross-modal representations are specifi c to complex dynamic stimuli [37] .As the contents of WM can be decoded from sensory cortices but not the PFC [31][32][33] , we propose here that, compared with the PFC, sensory cortices represent more precise information about the memorandum, and in this way serve as quality assurance in WM. …”
mentioning
confidence: 76%
See 2 more Smart Citations
“…However, at least for the within-vision stores, an alternative interpretation is that items from different categories show less interference than items from the same category, especially if, as recent brain imaging studies suggest, memory items are stored in those brain regions where they are processed to begin with (e.g., Lee, Kravitz, & Baker, 2013;Riggall & Postle, 2012;Sreenivasan, Vytlacil, & D'Esposito, 2014;Sreenivasan, Curtis, & D'Esposito, 2014):…”
Section: Chunkingmentioning
confidence: 99%